Contemporary Chinese education on screen: representations of Chinese educational experience in screen media from the 1980s to the 2000s - Wang, Ying (2024)
During China’s reform era from the 1980s to the 2000s, popular films addressed institutional transformations and the effects of change on Chinese people’s ordinary lives. This included transformations in the sphere of education, including the impact of key policies such as the restoration of the university entrance exam, the Opening-Up policy, urban and rural educational policies, and study abroad policies. Throughout a key period of social, political and economic transition in China, this thesis investigates screen media works from the 1980s to the 2000s as a site for dramatizing the experience of educational policy change. Using a case study approach, this thesis examines how screen representations negotiate cultural values around education in different periods of China’s economic transformation. Examining socio-economic dynamics and policy contexts within key reform era decades, it argues that screen media becomes a site where divergent educational experiences are represented, and ideological negotiations of value and self are worked through. By analysing strategic pairings of Chinese popular film and television series from the 1980s, 1990s and 2000s – illuminating different educational situations, school stages and policy settings – the thesis considers how Chinese cultural values of ambiguity, sacrifice, and the identity of self within interpersonal relationships, are used to represent different attitudes towards changes in Chinese education, which speak in turn to differing attitudes towards changes in China more broadly. In critical terms, the thesis demonstrates how institutional transformations, enacted through educational policy, are dramatized as individual stories and personalized experiences. In this way, the dissertation offers insights into the cultural and ideological work of popular screen media bridging official policy with everyday Chinese life.